Achieving model quality through model validation, verification and exploration. (December 2018) - Gogolla, Martin; Hilken, Frank; Doan, Khanh-Hoang
Abstract: System development strategies, like model-driven engineering (MDE), help to abstract architectures and provide a promising way to deal with architecture complexity and design quality. Thus, the importance for the underlying models to be correct arises. Today's validation and verification tools should support the developer in generating test cases and provide good concepts for fault detection. We here introduce and structure essential use cases for model validation, verification and exploration that help developers find faults in model descriptions and thus enhance model quality. Along with the use cases, we demonstrate a modern instance finder for UML and OCL models based on an implementation of relational logic and present the results and findings from the tool.